PARAMETRIC MODELING FOR SHAPE OPTIMIZATION - Bocharov, Sergey (Nazarbayev University School of Engineering and Digital Sciences, 2017)
Shape optimization has become a necessity in our pursuit for performance and efficiency in highly competitive fields ranging from engineering and science and finishing to medicine and agriculture. This plethora of shape-related problems gives rise to the requirement of flexible and generic frameworks that can address a wide series of problems. In our work, we closely examine the development of such a framework for the case of fluid flows around airfoils but we implement it in a way that would allow the extension of our approach to different areas of application. Commercial software packages like Solidworks or Ansys offer an advanced modeling and analysis environment but they do not come up with the required flexibility and customization capability demanded in our endeavor. On the other hand, the open source software package like OpenFOAM coupled with Matlab proved to be an efficient combination for our purposes. As a benchmark case for the framework, airfoil shapes are optimized at a single-point operating condition with fixed flow parameters. The Matlab's implementations for constrained nonlinear optimization drive the shape optimization process in our framework. The parametric model is based on the NURBS curve representation and the resulting airfoil instances are generated with the aid of eight parameters. Airfoil's performance is evaluated via appropriate flow analysis solvers for the selected range of applications. The framework's capabilities are demonstrated in the optimization of a given airfoil shape with respect to its lift coefficient. Specifically, a 4% increase is attained for the lift coefficient while the shape parameters are constrained to deviate up to 0.5% from the initial values.
Keywords: Shape optimization